Lhasa seismicity during 2004-2006 - Wangmo, Tsoja; Gelsor, Norsang; Havskov, Jens; Puntsog, Nima; Tsering, Baima (Journal of Nepal Geological Society, 2008)
The Tibetan Plateau is an active seismic region due to the collision between Indian and Eurasian plates. We have set up a new seismic network in the heart of the Tibetan Plateau, in the Lhasa region, to detect seismic activities. The measured data show that Lhasa is a seismically active region where at least 716 earthquakes were detected and a total of 218 events of magnitude greater than 2.0 occurred in the period between January 2004 and July 2006. Out of them, 11 earthquakes had a magnitude greater than 5.0. A high seismic activity was observed along the Dangshung fault zone.